1989
DOI: 10.1002/j.1552-4604.1989.tb03338.x
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of Citrate from Two Different Preparations of Potassium Citrate

Abstract: The bioavailability of citrate from two different preparations of potassium citrate was examined in eighteen normal volunteers during three phases of study. After stabilization on a constant metabolic diet, subjects took a single dose of placebo, “slow‐release” potassium citrate tablets (60 meq) or rapid‐release liquid potassium citrate preparation (60 meq). Timed urine specimens were collected for 24 hours and analyzed for citrate, potassium, and pH. Similar biochemical findings were observed following admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 5 publications
0
6
1
Order By: Relevance
“…This speculation, however, needs further investigation. Harvey et al [38] demonstrated that potassium citrate load caused a significant increase in urinary potassium up to 6 h, and also caused significant increase in urine pH. As a significant difference of increase in urine pH between LPR and water loads was not observed, an increase in urine pH after LPR and water loads that was found in this study may be due to the provided meals rather than water or LPR.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…This speculation, however, needs further investigation. Harvey et al [38] demonstrated that potassium citrate load caused a significant increase in urinary potassium up to 6 h, and also caused significant increase in urine pH. As a significant difference of increase in urine pH between LPR and water loads was not observed, an increase in urine pH after LPR and water loads that was found in this study may be due to the provided meals rather than water or LPR.…”
Section: Discussioncontrasting
confidence: 62%
“…Concentration of urinary citrate was maximized at 2 h after citric acid load [37]. We found the peak of urinary citrate concentration at 1 h after LPR load, and it persistently elevated for 2 h. Harvey et al [38] investigated the bioavailability of citrate from potassium citrate drugs in 18 normal volunteers and found that urinary citrate excretion was significantly increased at 1 h after dosing (60 mEq) and remained significantly high for 4-5 h. Although it cannot be directly compared, it is a clue that our LPR has a slightly lower bioavailability of citrate relative to the potassium citrate preparation. The actual reason remains to be elucidated.…”
Section: Discussionmentioning
confidence: 69%
“…Whereas urine of the Ank ank/ank mice still contained substantial amounts of citrate, that of the human patient lacking functional ANKH was virtually devoid of citrate. This difference might be partly explained by dietary differences: Citrate has a high bioavailability of 80-90% [24] and is present in standard rodent food. Possibly, the human patient with biallelic inactivating mutations in ANKH had a diet that was low in citrate, whereas part of the citrate detected in plasma of Ank ank/ank mice comes from dietary sources.…”
Section: Plos Geneticsmentioning
confidence: 99%
“…Existing alkalising agents are able to increase the urinary pH when compared to the corresponding placebo values but their duration of action is limited, requiring several daily administrations. The only alkalising therapy for which an extended release is claimed consists of a potassium citrate formulation (UROCIT-K tablets) but it has, however, been shown to exhibit a comparable profile to an immediate release liquid formulation of potassium citrate 20 . The period for which the urine pH was above 7.0 was short-lived and similar for both the liquid and the tablet formulation tested at the same dose (pH > 7.0 for only 3-4 h, approaching values observed in the placebo groups shortly thereafter).…”
Section: Discussionmentioning
confidence: 99%